Fractures and Subsequent Graft Loss and Mortality among Older Kidney Transplant Recipients. Issue 8 (6th May 2019) - Salter, Megan L.; Liu, Xinran; Bae, Sunjae; Chu, Nadia M.; Miller Dunham, Alexandra; Humbyrd, Casey; Segev, Dorry L.; McAdams‐DeMarco, Mara A.
Abstract : OBJECTIVES: Older adults who undergo kidney transplantation (KT) are living longer with a functioning graft and are at risk for age‐related adverse events including fractures. Understanding recipient, transplant, and donor factors and the outcomes associated with fractures may help identify older KT recipients at increased risk. We determined incidence of hip, vertebral, and extremity fractures; assessed factors associated with incident fractures; and estimated associations between fractures and subsequent death‐censored graft loss (DCGL) and mortality. DESIGN: This was a prospective cohort study of patients who underwent their first KT between January 1, 1999, and December 31, 2014. SETTING: We linked data from the Scientific Registry of Transplant Recipients to Medicare claims through the US Renal Data System. PARTICIPANTS: The analytic population included 47 815 KT recipients aged 55 years or older. MEASUREMENTS: We assessed the cumulative incidence of and factors associated with post‐KT fractures (hip, vertebral, or extremity) using competing risks models. We estimated risk of DCGL and mortality after fracture using adjusted Cox proportional hazards models. RESULTS: The 5‐year incidence of post‐KT hip, vertebral, and extremity fracture for those aged 65 to 69 years was 2.2%, 1.0%, and 1.7%, respectively. Increasing age was associated with higher hip (adjusted hazard ratio [aHR] = 1.37 per 5‐y increase; 95% confidence interval [CI] = 1.30‐1.45) and vertebral (aHR = 1.31; 95% CI = 1.20‐1.42) but not extremity (aHR = .97; 95% CI = .91‐1.04) fracture risk. DCGL risk was higher after hip (aHR = 1.34; 95% CI = 1.12‐1.60) and extremity (aHR = 1.30; 95% CI = 1.08‐1.57) fracture. Mortality risk was higher after hip (aHR = 2.31; 95% CI = 2.11‐2.52), vertebral (aHR = 2.80; 95% CI = 2.44‐3.21), and extremity (aHR = 1.85; 95% CI = 1.64‐2.10) fracture. CONCLUSION: Our findings suggest that older KT recipients are at higher risk for hip and vertebral fracture but not extremity fracture; and those with hip, vertebral, or extremity fracture are more likely to experience subsequent graft loss or mortality. These findings underscore that different fracture types may have different underlying etiologies and risks, and they should be approached accordingly. J Am Geriatr Soc 67:1680–1688, 2019